Gradual Acquisition of Professional Knowledge, Audit Quality and Audit Fees - Xu, Gaoshuang; Ding, Rui; Cheng, Hanxiu; Xing, Qiuhang (Frontiers in Psychology, 2022)
The acquisition of professional knowledge is the core issue studied in the formation of auditor industry expertise, but the previous literature has neglected the time required for auditors to acquire professional knowledge. We examine audit quality and audit fees of audit firms in different stages of auditor learning professional knowledge and find that in the initial stage of the process of learning knowledge, the audit quality and audit fees decrease. However, in the long run, the knowledge learning has a more obvious effect on the improvement of audit quality and audit fees, that is, the knowledge learning has a positive effect on the sustainable development of audit firms.